The collected poems - Price, Reynolds 1933-2011 (Scribner, 1997)
This volume presents the full range of Reynolds Price's poetic accomplishment over the past thirty-six years. His first three collections are brought together in their entirety; and a masterful new collection, The Unaccountable Worth of the World, is introduced. In his preface to The Collected Poems, Price credits guides as various as Miss Jane Alston, a public school English teacher in North Carolina, and W. H. Auden, one of his teachers at Oxford University: The sure trajectory of Price's development as a poet is traced from the "inexplicable elation" of his adolescent discovery of Emily Dickinson, to a lengthy immersion in John Milton's "polyphonic language, with its ready access to the eloquence of plain speech", to the four-stress rhythm of the Anglo-Saxons and Coleridge on which his work often continues to depend - that rhythm being "closely allied to the wary economy and dignity of those kinds of speech that, in my lifetime, have been most concerned for lucid and memorable communication". Those familiar with Price's earlier work will welcome having in one volume such vivid contributions as "The Annual Heron" (from Vital Provisions), "House Snake" (The Laws of Ice) and "An Afterlife, 1953-1988" (The Use of Fire). All will be introduced for the first time to his latest poems from the journal called "Days and Nights". This notebook was begun in the early 1980s, shortly before Price was diagnosed with a grave illness; and the entries continue in the second of three parts of The Unaccountable Worth of the World, many of them contending with the death of friends - "the Dying Belt, as my father called it". The whole new collection culminates in the powerful departures of such poems as "Scored by Light" and "The Closing, The Ecstasy".
Keywords: Geschichte 1900-2000; American poetry -- 20th century